Travelling Waves of a Diffusive Epidemic Model with Latency and Relapse - Zhiping Wang; Rui Xu (Discrete Dynamics in Nature and Society)
An SEIR epidemic model with relapse and spatial diffusion is studied. By analyzing the corresponding characteristic equations, the local stability of each of the feasible steady states to this model is discussed. The existence of a travelling wave solution is established by using the technique of upper and lower solutions and Schauder's fixed point theorem. Numerical simulations are carried out to illustrate the main results.